A RARE SEROTYPE SALMONELLA WELTEVREDEN CAUSING ENTERIC FEVER IN AN HIV POSITIVE PATIENT IN MANGALORE - M, Radhakrishna; KOTIGADDE S (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Enteric fever is endemic in India. Usually caused by Salmonella enterica serotypes Typhi and Salmonella enterica serotype Paratyphi A. Enteric fever due to non typhoidal salmonellae is rare. We report an extremely rare case of enteric fever caused by Salmonella enterica serotype Weltevreden in a HIV positive 27 year old male.